Transportation costs do matter: simulation study from hospital investment decision. (9th May 2016) - Hilmola, Olli-Pekka; Henttu, Ville
Abstract : Purpose: Most OECD countries will have a considerable challenge ahead with an ageing population and necessary health care produced for retired people. Healthcare costs have increased continuously from the mid-1990's in Finland, and growth is likely to continue in the future, as the amount of older inhabitants is increasing. Furthermore, transportation of patients and their visitors between homes and hospitals is a large component of the total health carehealth care related costs. This paper aims to estimate transport-related costs and develop ways to decrease these costs. Design/methodology/approach: A system dynamics simulation model was developed to examine different scenarios for patients and their visitor transportation to hospitals until the year 2040. Model is driven by age distribution of the region and likely by development of the total population. All parameter values were defined based on real-life observations. Findings: Patients' need to travel to hospitals is likely to continue to grow. In addition, quality of travel will change as older retired people are not willing or able to use their own transportation equipment or public transportation modes – this is the main reason for higher transportation costs of patients. Transportation is typically conducted via taxis, private cars and ambulances. Therefore, it is critical that people from the region are able to access hospital services with short proximity. Research limitations/implications: Simulation study is limited to one hospital investment decision in Finland. Distances and population densities as well as transportation mode alternatives differ from more populous regions in the world. Practical implications: Research findings stressed the importance of keeping their own hospital operations within the region and placing them in a better location. In an alternative case, where a hospital decision would have been abandoned, total transportation costs during 2012-2040 would have increased by at least the same amount that a new hospital is assumed to cost. Originality/value: This research is one of the first from the health care sector, where patient transportation modes and ageing is being dealt with in the context of new investments. Patient transportation is often an overlooked issue, which bears significant costs, especially as people age.